Mapping Localized Peroxyl Radical Generation on a PEM Fuel Cell Catalyst Using Integrated Scanning Electrochemical Cell Microspectroscopy - Edgecomb, Joseph; Xie, Xiaohong; Shao, Yuyan; El-Khoury, Patrick Z.; Johnson, Grant E.; Prabhakaran, Venkateshkumar (Frontiers in Chemistry, 2020)
Understanding molecular-level transformations resulting from electrochemical reactions is important in designing efficient and reliable energy technologies. In this work, a novel integrated scanning electrochemical cell microspectroscopy (iSECCMS) capability is developed by combining a high spatial resolution electrochemical scanning probe with in situ fluorescence spectroscopy. Using 6-carboxyfluorescein as a fluorescent probe, the iSECCMS platform is employed to measure the effect of the detrimental generation of reactive oxygen species (ROS) formed at the active sites of oxygen reduction reaction (ORR) catalysts. Carbon-supported tantalum-doped titanium oxide (TaTiOx) catalysts, a potential Pt-group-metal-free (PGM-free) cathode material explored for low temperature polymer electrolyte fuel cells (PEFCs), is used as a representative model ORR system, where generation of intermediate H2O2 instead of fully oxidized H2O is a major concern. We establish that the iSECCMS platform provides a novel and versatile capability for spatially resolved mapping of in situ ROS generation and activity during the kinetically-limited ORR and may, therefore, aid the future characterization and development of high-performance PGM-free PEFC cathodes.